Optical Properties of Co-doped Zinc Oxide Nanoparticles, Prepared by Pulsed Laser Ablation in Liquids - A.I. Savchuk; I.D. Stolyarchuk; B. Cieniek; A. Dzedisc; I.V. Hadzaman; I.S. Virt (Журнал нано- та електронної фізики)
Results of study of Zn1 – xCoxO nanoparticles, which were grown by pulsed laser ablation in liquid medium (PLAL), have been presented. Zn1 – xCoxO nanoparticles were produced by laser ablation of ceramic plates as targets in deionized water. The structural analysis using X-ray diffraction (XRD) of nanocrystals reveals the formation of predominant (002) reflection corresponding to the hexagonal wurtzite structure without any secondary phase. The performed scanning electron microscopy (SEM) analysis suggests of the well-defined flower-like nanoparticles. In optical absorption spectra of the colloidal nanoparticles short wavelength shift of the absorption edge due to confinement effect has been observed. With increasing of cobalt content the optical absorption spectra shown a red shift of the band edge which are caused by to the s, p-d exchange interactions between the band electrons and the localized spins of magnetic impurities. In the room temperature photoluminescence spectra of Zn1 – xCoxO nanoparticles four main peaks were revealed, which are attributed to the band - edge transitions and vacancies or defects